Evidentiary Barriers to Conviction and Two Models of Criminal Procedure: A Comparative Study - Damaska, Mirjan R (1973)
Comparative research of criminal justice systems is still in its infancy. It is not surprising, then, that when questions are asked transcending the concerns of a single system very little is actually known, and answers tend to be mostly in the nature of impressionistic beliefs and vague hypotheses. One such belief, frequently voiced, is that the rules of evidence under the common law adversary system of criminal procedure present much more formidable barriers to conviction than do corresponding rules in the non-adversary civil law system. This belief is then related to a more general feeling that the higher evidentiary barricades to conviction somehow emanate from the very nature of adversary proceedings and that their lowering smacks of the inquisitorial continental procedure. Both beliefs are interesting to a comparatist